Review on Knowledge Management and Employee Engagement - Sui, Hai Juan; Liu, Yao; Puteri Fadzline, Muhamad Tamyez; Ayodele, Freida Ozavize (2016)
Knowledge that resides in employees has been repeatedly convinced as a paramount resource for organizational competitive advantage. To this regards, the organization shall not just retain employees but also fully engage them, capture their minds and hearts which is scholarly called employee engagement. However, few researches have been explored to bridge managing knowledge and engaging employees. This paper reviewed literatures on employee engagement, knowledge management, and the impacts of knowledge management on employee engagement. It is expected to propose a conception that knowledge management practices could facilitate employee engagement. Hopefully, the proposed idea could enhance the organization’s awareness of knowledge management as a key approach to achieve competitive advantage.